Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.